Flat and convex photovoltaic cell collectors - Koo, Guo Qiang. (2010)
A study on photovoltaic cell has been carried out. Areas in which the efficiency and performance of the photovoltaic cell can be improved on have been researched and experimented. The aim of the research is to find out how the performance of the cell will be affected by the configuration of the photovoltaic cell i.e. a flat cell as compared to a convex cell with different curvatures.